ANALYSIS OF FACTORS CAUSING CORRUPTION BASED ON STREAMS IN CRIMINOLOGY - kres, kresnawati; Novi Sang Vitri; Zsa Zsa Nur Rafi'za; Ade Pramesty Dwi Pradika; Wajdi, Muhammad Farid (Realism: Law Review, 2025)
In the realm of criminology, there are several schools that have different opinions on criminology. In addition to the Juridical (Law) stream, there is a non-Juridical school which is better known as the Sociological school. One scholar of the Sociological stream, Thorsten Sellin, as quoted by Topo Santoso, argued that a better basis for the development of scientific categories is to provide a better basis by studying conduct norms, because the concept of behavioral norms which includes every group or institution such as the state and is the creation of any normative groups, and is not confined by political boundaries and does not always have to be contained in law. The critical criminology approach is more comprehensive than the classical approach which places more emphasis on juridical aspects. A critical approach that covers the root causes of crime and involves authorities such as labor owners is seen as having relevance in overcoming crime (corruption) in Indonesia.